FOOD SECURITY IN THE CONTEXT OF WAR IN UKRAINE: ECONOMIC AND LEGAL ASPECTS - Olena Hafurova; Volodymyr Yermolenko; Iryna Yermolenko (Baltic Journal of Economic Studies)
The need to study the economic and legal issues of Ukraine's food security and ensure an adequate level of availability and sufficiency of food for the population at the present stage is caused by a number of factors. A prominent place among them is occupied by the challenges caused by the war that has been going on in Ukraine for many years. The food security situation in the country is rapidly deteriorating in the context of a full-scale war, and in some regions (especially those affected by military operations) it is catastrophic. At the same time, the pre-war food security legislation is not able to properly regulate existing relations. Similarly, research conducted in peacetime has largely lost its relevance. Thus, the topic of this article is relevant and the research is timely. Its purpose is to analyse the regulatory framework for food security, identify key shortcomings and formulate proposals for their elimination. The study is based on a set of methods of scientific knowledge, in particular: the philosophical dialectical method, the method of analysis, formal legal and formal logical methods. Results. The article establishes that in Ukraine the provision of such food security indicators as: daily energy value of the human diet; provision of the human diet with basic types of food; economic affordability of food is at a low level. It is proved that one of the reasons for this is the imperfection of regulatory support. The paper reveals the absence of such important features as ‘safety’ and ‘quality’ of food in the legislative definition of the concept of ‘food security’. Attention is focused on the risks of simplifying the rules for handling genetically modified organisms in the context of food production. Practical implications. The publication substantiates the need to develop and adopt a State programme for ensuring food security, which should be targeted and designed for a long-term period. This will, firstly, make it possible to clearly define the priority of food security in the social and economic policy of Ukraine; secondly, it will make it possible to clearly define the measures to ensure food security, the executors, the timing and other necessary criteria.